Konsep Pendidikan Humanisme Paulo Freire Dalam Perspektif Pendidikan Islam - Abdillah, Syaik; Rofiq, Hilman Muhammad (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
In the era of Disruption 5.0, where convenience is abundant, society faces a dichotomy of positive and negative values emerging within the community. The positive impacts of this disruptive era include changes in values and attitudes, the advancement of science and technology, and improved living standards. Conversely, the negative repercussions are evident in the decline of national moral quality, as seen in the increasing number of cases that deviate from societal norms and values. Paulo Freire, a prominent figure in educational philosophy, advocated for a critical alternative education model, which has been praised for addressing issues within formal education systems. On the other hand, Islamic education is inherently rich with transcendental, divine, and humanistic values. These can be encompassed within the broader framework known as theocentric humanism or religious humanism, an effort to integrate religious and divine values. A concept or educational theory lacks significant social impact unless oriented towards action. To emphasize the need for action, these theocentric humanistic values are proposed as an ideological paradigm for Islamic education. The objective of this study is to describe Paulo Freire's concept of humanistic education from the perspective of Islamic education. The research method employed is library research, which involves utilizing library resources to obtain the necessary data through a sequence of activities related to literature review, reading, note-taking, and processing the required research materials. The results of this study indicate both similarities and differences between Paulo Freire's concept of humanistic education and Islamic education. The similarities lie in their focus on developing students' potential according to their interests and talents. The key difference is that Freire's Humanistic Education emphasizes the psychological aspects of students, whereas Islamic Education emphasizes a balance between the affective and cognitive domains of students. Keywords: Paulo Freire's Humanistic Education, Islamic Education